(untitled) (Journal of Science and Technology, 2016)
Throughout the world today, one major problem facing almost all Universities is that of inadequate resources to support both academic and research work. This is one particular issue which affects both the developed and the developing countries. The magnitude however may vary from country to country and from one University to another. An attempt has been made in this paper to identify some problems of resource allocation in the University, especially the University in the developing countries, and to offer suggestions.